Macrozoque hoplandrioides (Coleoptera: Staphylinidae: Aleocharinae), a new genus and species of false Lomechusini from México - Santiago-Jiménez, Quiyari J. (Zootaxa, 2016)
Macrozoque hoplandrioides n. gen. and n. sp. (Coleoptera: Staphylinidae: Aleocharinae), is described based on specimens recently collected from the Chimalapas forest in Mexico. The systematic position of Macrozoque is discussed and is proviosionally placed in the false Lomechusini clade. A distribution map, keys and illustrations are provided.